Nature: capturing Sarawak's visual heritage / Dr. Muhamad Hafiz Hassan - Hassan, Muhamad Hafiz (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
In the vibrant tapestry of Sarawak's artistic expression, nature emerges as a profound and multifaceted muse. The artworks in this exhibition reveal a deep connection between the land, its inhabitants, and the creative spirit that flourishes in this corner of Borneo. From the enigmatic Rafflesia, the world's largest flower, to the carnivorous pitcher plants that inspired poetic musings, the flora of Sarawak captivates our imagination. Artists have employed various techniques, from pouring acrylic on canvas to create abstract representations, to meticulous brushwork that captures the intricate details of these botanical wonders. The fauna of the region holds equal prominence. The majestic hornbill, Sarawak's emblematic bird, appears not just as a subject but as a symbol of strength, courage, and community. The crocodile, adorned with a floral halo, represents the intricate relationship between humans and nature, embodying both respect and caution. Even the humble cat finds its place, dressed in traditional attire, bridging culture and nature in whimsical yet meaningful ways. The feline figures serve as light-hearted reminders of Kuching's name, connecting local folklore and artistic expression. UiTM Sarawak has achieved and structured in its policies towards greening